Risk factors for mortality in culture-negative neonatal sepsis in Malawi: a propensity score-matched analysis - James Chirombo; Pui-Ying Iroh Tam; Kondwani Kawaza; Tessa de Baat; Lughano Ghambi (BMJ Publishing Group, 2024)
We conducted a propensity score-matched multivariable regression analysis of 1050 culture-negative neonatal sepsis cases in Malawi, where 160 (15.2%) died. Mortality among neonates with culture-negative sepsis was associated with very low birth weight (adjusted OR (AOR) 12.82, 95% CI 1.23 to 137.49), respiratory distress syndrome (AOR 13.20, 95% CI 2.58 to 83.66), a low Apgar score at 1 min (AOR 3.50, 95% CI 1.21 to 10.72) and at 5 min (AOR 4.77, 95% CI 1.94 to 12.50). Addressing maternal and perinatal factors around health and delivery of care is key to improving outcomes in the context of culture-negative sepsis in neonates from low-income country settings like Malawi.